Pleomorphic rhabdomyosarcoma with pulmonary tumour embolism. (30th November 2012) - Abdulaziz, Salman; Geddawy, Mohammed; Al Efraij, Khalid; Jamil, Mouhamad Ghyath
Abstract : Pulmonary tumour embolism is a known complication of cancer disease. To date, pleomorphic rhabdomyosarcoma has been described once with this entity. We report a case of pulmonary tumour embolism diagnosed in the operation room after cardiac arrest of a 30-year-old male patient who had surgical amputation of his right upper limb due to recurrent sarcoma, mandating urgent and successful embolectomy.